The Burial Under Peat Technique: An Innovative Method to Restore Sphagnum Peatlands Impacted by Mineral Linear Disturbances - Pouliot, Kathy; Rochefort, Line; LeBlanc, Marie-Claire; Guêné-Nanchen, Mélina; Beauchemin, Alexandre (Frontiers in Earth Science, 2021)
Mineral roads in peatlands change the nature of the substrate, influence the water table level of the peatland on either side of the road and the physicochemical characteristics of the water and peat. These changes can in turn affect plant community composition. The efficiency of an innovative and affordable method for the restoration of peatlands impacted by roads was evaluated: the Burial Under Peat Technique. To be considered effective from an ecological point of view, the technique should meet restoration goals by 1) confining the chemical elements and compounds potentially leaching from the mineral material; 2) creating and maintaining a restored surface elevation similar to the adjacent peatland for optimal rewetting; and 3) re-establishing typical peatland vegetation communities. Three years post-restoration, water sampled at various depths and distances to the buried road presented chemical elements and compounds concentrations similar to the means measured in the pristine surrounding peatland for most of the ions analyzed. The different steps of the technique ensured the reestablishment of an elevation similar to the surrounding peatland. The return of peatland plant communities was slow, mainly due to local factors (e.g., presence of drainage ditches). Furthermore, the Burial Under Peat Technique fulfilled the restoration objectives in re-establishing an acid organic soil. Finally, it is cost-effective method in comparison to completely removing the mineral material and transporting new material to fill the depression left by the excavation of the road.